2017
DOI: 10.1017/cem.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

Simulation in Canadian postgraduate emergency medicine training – a national survey

Abstract: SBE is frequently used by Canadian FRCPC-EM residency programs. However, there exists considerable variability in the structure, frequency, and timing of simulation-based activities. As programs transition to competency-based medical education, national organizations and collaborations should consider the variability in how SBE is administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
1
34
0
4
Order By: Relevance
“…At several sites across Canada, this urgency has helped overcome typical barriers to simulation-based education, such as faculty buy-in, time, and resource allocation. As a result, EDs across the country are shifting resources, equipment, and personnel from existing programs of simulation-based education 4,5 and implementing COVID-19-focused simulation-based training for their clinical teams at an unprecedented pace (e.g., some locations are conducting daily simulations within their departments).…”
Section: Simulation For Educationmentioning
confidence: 99%
“…At several sites across Canada, this urgency has helped overcome typical barriers to simulation-based education, such as faculty buy-in, time, and resource allocation. As a result, EDs across the country are shifting resources, equipment, and personnel from existing programs of simulation-based education 4,5 and implementing COVID-19-focused simulation-based training for their clinical teams at an unprecedented pace (e.g., some locations are conducting daily simulations within their departments).…”
Section: Simulation For Educationmentioning
confidence: 99%
“…Simulation has played an increasing role in medical education and provides opportunities to practice high-risk scenarios in a low-risk, high-fidelity environment. [10][11][12] Although residents are unable to attend sessions at simulation centres due to COVID-19 restrictions, simulation continues to play an important role in resident education. Many departments have accelerated their in situ simulation programs in response to COVID-19 for protocol development and revision, provider training, and teambased training.…”
Section: Simulationmentioning
confidence: 99%
“…In U.S. and Canadian paediatric emergency medicine, SBMT was being provided by 97% of residency programmes in the 2011–2012 academic year [9]. Recent surveys showed that SBMT is used by more than 90% of U.S., Canadian and English-language-based emergency medicine residency programmes, even though a considerable variability in the accreditation and certification, and frequency and timing of SBMT has been highlighted [10, 11].…”
Section: Introductionmentioning
confidence: 99%